(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2025)
The Intensive Care Unit (ICU) is an area of the hospital that specializes in caring for patients suffering from traumatic illnesses or serious, life-threatening complications. Families in this situation often face various psychological problems such as acute stress, post-traumatic stress, anxiety, and depression. This study aims to determine the relationship between family involvement and the Psychological Condition of Families of Patients Hospitalized in the Intensive Care Unit. This study is a quantitative study using a cross-sectional design. The analysis used is Univariate and Bivariate Analysis using the Chi-Square test. The results of the statistical test of the relationship between family involvement and anxiety level obtained a p value of 0.570 > 0.05 so that H0 failed to be rejected, meaning that there was no significant relationship between family involvement and anxiety level. While the results of the statistical test of the Relationship between Family Involvement and Stress Level, the p value of 0.350 < 0.05 so that H0 is rejected, meaning that there is a significant relationship between family involvement and stress level. The study shows that family involvement has a significant effect on the stress level of the patient’s family, but not on the level of anxiety in the family. Future research is expected to discuss interventions that can facilitate information needs for families in the intensive care unit.